If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = cosx + tan(2x) Remove parenthesis around (2x) Y = cosx + ant * 2x Reorder the terms for easier multiplication: Y = cosx + 2ant * x Multiply ant * x Y = cosx + 2antx Reorder the terms: Y = 2antx + cosx Solving Y = 2antx + cosx Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 2antx + cosx
| 0.02*x=300 | | x^2+4y-1=0 | | 2u^2-2u-12=u^2-9 | | 12x-28=20 | | 120(2/5) | | 39-12w=7-4w | | -4.5r=-13.95 | | 17(t-3)+4t=7(3t+5)-12 | | 12+2+x=4y+x+2 | | -4.5=-13.95 | | 2+3+7+8-10= | | 27.03=x-17.65 | | 5x+x=20+x | | 3/13p=-9/4 | | 2y=2x-20 | | -16=4x/3 | | 6yx-12y=0 | | 6yx-12x=0 | | k=0,1,2,1/2,-1-2 | | --8=4x/9 | | 0=-16x^2+90x | | 5=.1*x | | 44/8= | | 4.8=.9*x | | y=-16+90 | | -5/12y≤25 | | 40-5x+7=0 | | 2w^2+5w+3=0 | | 4x+6=2(x+7) | | 2x^3-x^2-10x-7=0 | | -3(6-x)-3=x-4 | | 8(x+3)=8x+2x |